Critical Analysis of the Tools of Achieving Truth in the Philosophy of Science - Nur Fatimatul Zahra; Rizqi Syahrur Ramadhan; Tamsik Udin (Bibliotheca: Journal of Philosophy, 2026)
This paper examines the Critical Analysis of the Tools for Achieving Truth in the Philosophy of Science. The search for truth in the realm of science is not a linear journey relying on a single tool, but rather a complex and dynamic dialectical process. From the discussion that has been conducted, several main conclusions can be drawn. First, Rationalism and Empiricism are two fundamental epistemological pillars that, although seemingly contradictory, both make invaluable contributions. Second, Karl Popper's idea of ​​Falsification marks a crucial leap in our understanding of scientific truth. Third, the thoughts of post-Popper philosophers such as Thomas Kuhn and Imre Lakatos enrich and nuance the picture. Fourth, this picture is made more complete by recognizing the existence of radical perspectives and informal "tools" that often trigger progress. Fifth, and no less importantly, all these philosophical debates prove to be alive and relevant in facing the challenges of contemporary science. Modern issues such as the debate over the scientific status of Theory Ultimately, the "tools for achieving truth" are not one golden hammer, but a diverse toolbox. Solid scientific truth is built from a combination of rational imagination, solid empirical evidence, relentless falsifiable criticism, and an awareness of the paradigms that surround it.